2014
DOI: 10.1016/j.ypmed.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

The health consequences of child mental health problems and parenting styles: Unintentional injuries among European schoolchildren

Abstract: Objective Unintentional injury is the leading cause of death for schoolchildren. We assessed the association between externalizing psychopathology, parenting style, and unintentional injury in European children in the community. Methods Data were drawn from the School Children Mental Health in Europe project and included 4517 schoolchildren across seven diverse European regions. Past year injuries serious enough to seek medical atten tion were reported by mothers. Child mental health problems were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 81 publications
2
34
1
1
Order By: Relevance
“…Our findings confirmed that emotional symptoms, conduct problems and hyperactivity were significantly associated with unintentional injury, which was demonstrated by prior studies (Keyes et al 2014;Lalloo et al 2003). Lalloo reported that English children who scored high for emotional symptoms and hyperactivity were 1.5 times more likely to report minor accidents (Lalloo et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings confirmed that emotional symptoms, conduct problems and hyperactivity were significantly associated with unintentional injury, which was demonstrated by prior studies (Keyes et al 2014;Lalloo et al 2003). Lalloo reported that English children who scored high for emotional symptoms and hyperactivity were 1.5 times more likely to report minor accidents (Lalloo et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The annual prevalence of unintentional injury among 5 to 9 grades schoolchildren in Yinzhou was revealed 38%, which was higher than that in Europe (17.3%) (Keyes et al 2014), Canada (24%) (Gilbride et al 2006), and Jordan (33.9%) (ALBashtawy et al 2016), but lower than Yemen (48%) (Alshahethi 2014) and Thailand (46.8%) (Peltzer and Pengpid 2012). The prevalence was also higher than prior similar studies in China.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Individual risk factors for children include being male [8], being of a higher birth order [9], and externalizing problems [10], while individual risk factors for parents are young maternal age [9], low education level [11], and maternal depression [9,12,13]. Risk factors for households include low socioeconomic status [14], and highly stressful or adverse life events in the family [8,15].…”
Section: Introductionmentioning
confidence: 99%